1995
DOI: 10.1161/01.cir.91.2.426
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Left Ventricular Hypertrophy and Its Regression on Ventricular Electrophysiology and Vulnerability to Inducible Arrhythmia in the Feline Heart

Abstract: LVH produces multiple electrophysiological abnormalities and increased vulnerability to inducible polymorphic ventricular arrhythmia in this model of LVH. Cats that show regression of hyperthrophy have normal ventricular electrophysiology and have the same low vulnerability to inducible ventricular arrhythmia as Sham animals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
36
1
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(41 citation statements)
references
References 23 publications
2
36
1
2
Order By: Relevance
“…Reduction of systolic BP can reduce the risk of stroke and heart failure in hypertensive older individuals (2,4). Furthermore, regression of LVH is likely to reduce cardiovascular risks in hypertension (40).…”
mentioning
confidence: 99%
“…Reduction of systolic BP can reduce the risk of stroke and heart failure in hypertensive older individuals (2,4). Furthermore, regression of LVH is likely to reduce cardiovascular risks in hypertension (40).…”
mentioning
confidence: 99%
“…28 Besides its blood pressure-raising effects, AngII is a potent growth-stimulating peptide and plays a crucial role in the development of LVH. [3][4][5]17,29 Therefore, in the TAC mouse model, the AngII-mediated pathway may be a critical determinant of LVH. Rials and his colleagues reported that long-term treatment with ACE inhibitors prevented or reversed LVH as well as associated structural and functional abnormalities in the reno-vascular hypertensive rabbit model.…”
Section: Discussionmentioning
confidence: 99%
“…Such a result, qualitatively similar to those reported in the rat atrium and attributed to an agedependent prolongation (3), could possibly be explained by a decrease in the density of I to1 during this period (see below). Previous studies used surgical (2,18) or pharmacological methods (19,20,28) to produce regression of hypertrophy and reported a concomitant normalization of ventricular APD. It was then hypothesized that any intervention that produces regression of hypertrophy restores ventricular electrophysiology, that is to say that the regression of hypertrophy is responsible for the normalization of electrophysiological parameters (19).…”
Section: Discussionmentioning
confidence: 99%
“…This morphological normalization occurred at both the level of muscular tissue, as shown by the decrease toward control values of some myocyte parameters (perimeter, capacitance, and width), and the level of the interstitial collagenous connective tissue. In the chronic high-altitude hypoxia model, the regression of right ventricular hypertrophy would not be a prerequisite for normalization of ventricular electrophysiological abnormalities.hypertrophy; right ventricular myocytes; fibrosis; action potential; ionic currents RECENT EVIDENCE in animal models of left ventricular (LV) hypertrophy (LVH) suggests that LVH regression is associated with normalization of ventricular electrophysiology (18,19,28). Chronic hypoxia is the main pathophysiological factor in severe disturbances of the cardiovascular system, represented by pulmonary, ischemic, and congenital heart disease and in cardiopulmonary changes induced by exposure to a high-altitude environment (17).…”
mentioning
confidence: 99%
See 1 more Smart Citation